2007
DOI: 10.1002/adma.200601882
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of Mesoscale Polymer Patterns in an Evaporating Bound Solution

Abstract: The use of spontaneous self-assembly as a lithography-and external-fields-free means to construct well-ordered, often intriguing structures, has received much attention owing to the ease of producing complex structures with small feature sizes. [1][2][3] Drying mediated self-assembly of nonvolatile solutes (polymers, nanoparticles, and colloids) through irreversible solvent evaporation of a sessile droplet on a solid substrate (unbound solution) represents one such case. [3][4][5][6][7][8][9][10][11][12][13][1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
117
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 34 publications
5
117
0
6
Order By: Relevance
“…The model incorporates wettability, capillarity, evaporation, convective transport of the solution and diffusion of the solute and has been derived employing a long-wave approximation. We find that a strong nonlinear dependence of viscosity (i.e., the front mobility) on concentration triggers, in an intricate interaction with evaporation and diffusion, the deposition of periodic and aperiodic line patterns as observed in experiments for many different materials and settings [2,[5][6][7][8][9][10][11]30]. We believe that the model explains a basic mechanism for the formation of regular line patterns.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…The model incorporates wettability, capillarity, evaporation, convective transport of the solution and diffusion of the solute and has been derived employing a long-wave approximation. We find that a strong nonlinear dependence of viscosity (i.e., the front mobility) on concentration triggers, in an intricate interaction with evaporation and diffusion, the deposition of periodic and aperiodic line patterns as observed in experiments for many different materials and settings [2,[5][6][7][8][9][10][11]30]. We believe that the model explains a basic mechanism for the formation of regular line patterns.…”
mentioning
confidence: 85%
“…The occurrence of regular stripe patterns is a somewhat generic phenomenon, that is not only observed for different combinations of substances but also in a variety of experimental setups that allow for slow evaporation. Examples include the meniscus technique in a sphere-on-flat geometry [7,9], a controlled continuous supply of liquid between two sliding plates to maintain a meniscus-like surface [5] and dewetting forced by a pressure gradient [10]. Interestingly, besides the stripes parallel to the receding contact line, a variety of other patterns are observed, including regular orthogonal stripes [9], superpositions of orthogonal and parallel stripes [5], regular arrays of drops [5,14] and irregularly branched structures [14,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 In our previous work, we reported that concentric rings of electrically conducting polymer and organometallic polymer of high regularity were formed naturally and spontaneously via controlled, repetitive "stick-slip" motion of the three-phase contact line when a drop of polymer solution was confined either between two crossed cylindrical mounts covered with single crystals of mica sheets 10 or between a spherical lens made of silica and a Si substrate (sphere-on-flat geometry), resulting in a capillary-held polymer solution (i.e., capillary bridge). [11][12][13][14][15][16][17] The evaporation in this geometry was restricted to the edge of the droplet, and the "stick-slip" cycles resulted in hundreds of concentric rings with regular spacing, very much resembling a miniature archery target. Each ring was nanometers high and several microns wide.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] By tuning the interfacial interaction between the polymer and the substrate that governed the stability of thin films, intriguing, ordered dissipative structures can be produced as a result of synergy of controlled self-assemblies of the polymer and its destabilization mediated by the interfacial interaction. 15 We have reported that the use of solutions with different concentrations and different solvents effectively mediated the pattern formation in an evaporating droplet containing nonvolatile solutes. 11 In this paper, we extend our previous work to investigate the molecular weight (MW) effect on the mesoscale polymer patterns formed by drying a drop of polymer solution in a sphere-on-flat geometry (i.e., a spherical lens (or a pushpin) on a Si substrate), as depicted in Figure 1.…”
Section: Introductionmentioning
confidence: 99%